Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

South Asian transnational marriages in comparative perspective - CHARSLEY, KATHARINE; SHAW, ALISON (Global Networks, 2006)
Abstract This issue on South Asian transnational marriages brings diverse practices and networks into detailed ethnographic focus. Gender and agency are key themes explored in the collection, as well as the potential and actual transformation of gendered status resulting from marrying a migrant or joining a spouse overseas. The introduction identifies some common threads. Several articles challenge the assumption of wives' passivity in arranged marriages or in their joining husbands overseas, while one highlights the less-documented experiences of men who migrate to join wives working abroad. The collection also offers insights into the cultural and emotional reasons for such marriages, complementing analyses that stress strategic motivations, and noting the emotional consequences of separation and new household formations for the experiences of marriage and parenthood. Marriage emerges as an important means of producing and transforming transnational networks, while marriage practices and dynamics are themselves transformed in the process.
Keywords: 2000 à aujourd'hui; 2000-2009; anthropologie; approches et analyses; asie; asie du sud; cours; discipline; ethnographie; histoire et politique; mariage; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis